Implementasi Konsep Islam Rahmatan lil 'Alamin dalam Pendidikan Karakter di SDN Seneng 1 Krucil Probolinggo - Miftahul Hasan; Ainur Rofiq Sofa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to analyze the implementation of the Rahmatan lil 'Alamin Islamic concept in character education at SDN Seneng 1 Krucil Probolinggo. The study highlights the importance of applying Islamic values that bring mercy to all of creation as a foundation for shaping students' character with tolerance and noble ethics. The research methodology is qualitative, using a case study approach, involving Islamic Religious Education teachers and the principal as the research subjects. Data were collected through interviews, observation, and documentation. The results show that the implementation of the Rahmatan lil 'Alamin concept at SDN Seneng 1 Krucil has had a positive impact on shaping students' character. This concept teaches religious values that prioritize compassion, interfaith tolerance, and peace in daily life. Furthermore, students are encouraged to develop empathy, respect, and become agents of change for the benefit of society. The study concludes that the Rahmatan lil 'Alamin concept can serve as a guideline for character education to create a generation with noble morals who can live harmoniously in a pluralistic society.